Amino acids adsorption in differently aged and concentrated aqueous suspensions of ZnO and TiO[2] nanoparticles - Papina J.; Godymchuk (Godimchuk) A. Yu. Anna Yuryevna; Kutukov A.; Kuznetsov D.; Baisalova G. (2019, 2019)
Title screen